Incidence and Risk Factors of Surgical Site Infection After Knee Arthroplasty; a Systematic Review and Meta-Analysis - Bagheri , Ayub; Sharifi Niknafs, Alireza; Farhadi, Bahar; Mazhari, Seyed Amirhossein; Karimian, Parnia; Hekmati Pour, Nafiseh; Hojjati, Hamid; Nosratabadi, Iman; Emami , Azadeh; Salehi, Reza (Archives of Academic Emergency Medicine, 2025)
Introduction: Surgical site infection (SSI) constitutes a substantial complication after knee arthroplasty, contributing to notable morbidity. This study aimed to review the existing literature on the incidence and risk factors of SSI following knee arthroplasty. Methods: A systematic search was undertaken across various international electronic databases, including Scopus, PubMed, Web of Science, and Persian electronic databases such as Iranmedex and the Scientific Information Database. The search strategy involved the use of keywords derived from Medical Subject Headings, such as “incidence”, “Surgical wound infection”, “Surgical site infection”, and “Arthroplasty”, covering records from the earliest available up to March 17, 2024. Results: The study incorporated a collective participant group of 1,366,494 knee arthroplasty procedures from twenty-three chosen studies. The pooled incidence rate of SSI after knee arthroplasty was 1.7% (95% confidence interval (CI): 1.1% to 2.6%; I²=99.687%; P<0.001). The Odds Ratio (OR) for the incidence of SSI in males was observed to be significantly higher than that in females (OR: 1.617; 95% CI: 1.380 to 1.894; Z=5.951; P<0.001). The pooled incidence of SSI among diabetic patients was 1.3% (95% CI: 0.6% to 2.8%; I²=99.126%; P<0.001). Conclusion: Based on the main findings, SSIs continue to be a significant complication of knee arthroplasty, with an incidence of 1.1% to 2.6%. Male gender and diabetes mellitus were associated with an augmented probability of SSIs following knee arthroplasty.